The Values of Educational Character in the Arabic Temples of Qasidah Burdah by Imam Bushiri - Furqon, M. Rizalul; Fauzi, Moh. Fery (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2019)
This research aimed to determine the values of educational character in the Arabic temples of Qasidah Burdah by Imam Bushiri. The method used in this research was the descriptive analytical approach, which relies on the study of reality and phenomenon as it exists in reality and was concerned as an accurate description and expressed qualitatively and quantitatively. The results of the research were that the poem of Bosiri filled with rich educational behavioral values because many people read this poem and do not know its content and meaning in detail. Behavioral educational values in the poem of Bosiri are divided into four elements: 1) Behavioral educational values divinity, 2) personality, 3) social, 4) and moral. The verses concerning the behavioral educational values in this poem eighty-two beta.